COVID-19 Is Transforming Economic Policy in the United States - Claudia Sahm (Intereconomics, 2021)
Cutbacks in government spending slowed the recovery and led to lasting damage to workers and economic growth.
Keywords: 330; Coronavirus; Epidemie; Wirtschaftspolitik; USA